The changing structure of local credit markets: Are small businesses special? - Bonaccorsi di Patti, Emilia; Gobbi, Giorgio (Journal of Banking & Finance, 2001)
In many countries consolidation in the banking industry has reduced the number of small banks and led to significant shifts in market shares; deregulation has fostered entry in local credit markets and the expansion of branch networks, increasing competition in local markets. Small businesses are believed to be more vulnerable to these changes, since they are more dependent on credit from local banks. In this paper we investigate the consequences of consolidation and entry for these borrowers compared with those for large firms. We employ a data set for Italy, which provides information on volumes of loans and bad loans by size of borrower with a detailed geographical partition. We find that mergers are followed by a temporary reduction in outstanding credit to all sizes of borrowers and by an increase in bad loans, most likely due to the reassessment of banks portfolios. Entry has a relatively persistent negative impact on credit supply to small and medium-sized firms. Our results also show that concentration, branch density and the share of branches of small banks affect the volumes of credit and bad loans of small borrowers.